Transcriptional profiling of CcpE-regulated genes in Staphylococcus aureus - Li, Han (Genom Data, 2015)
The transcriptional regulator CcpE is an important citrate-sensing regulator that modulates metabolic state, virulence factor expression, and bacterial virulence of Staphylococcus aureus (Ding et al., 2014 [1]). In this article, we report detailed methods for genome-wide transcriptional profiling of CcpE-regulated genes generated for the research article “Metabolic sensor governing bacterial virulence in Staphylococcus aureus” (Ding et al., 2014 [1]). All transcriptional profiling data was deposited to Gene Expression Omnibus (GEO) database under accession number GSE57260.